Poorly controlled diabetes during pregnancy and lactation activates the Foxo1 pathway and causes glucose intolerance in adult offspring - Inoguchi, Yukihiro (Sci Rep, 2019)
Exposure to maternal diabetes during pregnancy results in diabetes in offspring, but its underlying mechanisms are unclear. Here, we investigated the phenotype and molecular defects of the offspring of poorly controlled diabetic female mice generated by streptozotocin (STZ) administration. Offspring was exposed to maternal diabetes during pregnancy and lactation. The body weight of STZ offspring was lower than that of control offspring at birth and in adulthood, and glucose tolerance was impaired in adult STZ offspring. Interestingly, the phenotype was more pronounced in male offspring. We next investigated the morphology of islets and expression of β cell-related genes, but no significant changes were observed. However, transcriptome analysis of the liver revealed activation of the fork head box protein O1 (Foxo1) pathway in STZ male offspring. Notably, two key gluconeogenesis enzyme genes, glucose 6 phosphatase catalytic subunit (G6pc) and phosphoenolpyruvate carboxykinase 1 (Pck1), were upregulated. Consistent with this finding, phosphorylation of Foxo1 was decreased in the liver of STZ male offspring. These changes were not obvious in female offspring. The activation of Foxo1 and gluconeogenesis in the liver may have contributed to the impaired glucose tolerance of STZ male offspring.